(untitled) (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2025)
Student-centered learning has become a prominent focus in modern education, encouraging approaches that promote learners’ active participation and emotional engagement. Mindful learning, which emphasizes awareness, reflection, and present-moment focus, has been shown to support these goals. However, few studies have explored how it is practically implemented in English Language Teaching (ELT) classrooms. This study aims to investigate the implementation of mindful learning strategies in English Language Teaching (ELT) and their impact on student motivation and engagement. Using a mixed-methods approach, the research involved one English teacher and 30 eighth-grade students at MTS Muslimin Indonesia Center Samarinda. Data were collected through classroom observations, semi-structured interviews, and pre- and post-intervention student motivation and engagement questionnaires. The observation results revealed that teachers had begun to apply mindful learning principles such as focused attention and reflection, although not yet in a systematic manner. Major challenges faced by teachers included time constraints, lack of formal training, and initial resistance from students. Quantitative analysis showed a significant increase in student motivation and engagement scores following the implementation of mindful learning strategies. These findings support the application of mindful approaches in ELT and highlight their benefits for enhancing students’ learning experiences. The study also emphasizes the need for institutional support and structured teacher training to ensure more effective implementation of this approach.